Front Cover: Direct measurement of enthalpy and entropy changes in NH3 promoted O2 activation over Cu−CHA at low temperature (ChemCatChem 11/2021). Issue 11 (17th May 2021) - Wang, Xueting; Chen, Lin; Vennestrøm, Peter N. R.; Janssens, Ton V. W.; Jansson, Jonas; Grönbeck, Henrik; Skoglundh, Magnus
Abstract : The Front Cover shows an oxygen molecule activated on a pair of Cu‐ammonia complexes in a chabazite cage, which is an important reaction intermediate in ammonia‐assisted NOx reduction over Cu‐chabazite. In their Full Paper, X. Wang, L. Chen et al. investigate the heat generated through the oxygen activation process over Cu‐ammonia complex pairs in chabazite. The authors present measurements and first principle calculations of the adsorption enthalpy and entropy. Their results show that oxygen activation is promoted by the Cu‐ammonia complexes thanks to the mobility of these Cu species in chabazite. More information can be found in the Full Paper by X. Wang, L. Chen et al.